COMPROMISO ORGANIZACIONAL DE LOS TRABAJADORES DE LA EMPRESA "INNOVA" CENTRO CERÁMICO - AGUIRRE DIAZ, MAXIMO LENIN (2018)
he company Innova Centro Cerámico dates back to 1985, in the city of La Troncal, in the province of Cañar, founded mainly as a hardware store, a family business that over the years was very well received within its city and nearby sectors. That is how MOBILTROICORP S.A. Legally born in 2010 in the city of Guayaquil, the commercial name acquired was INNOVA CENTRO CERAMICO, and the main activity that would be dedicated to the marketing and distribution of all types of materials and finishes for construction, attention personalized and technical advice.